Comprehensive Clinical Evaluation and Management of Severe Autoimmune Hemolytic Anemia: A Case Study of a 39-Year-Old Female with Anemia Gravis and Cultural "Susuk" Implantation - Veronica Debora (The International Journal of Medical Science and Health Research, 2026)
Introduction Autoimmune hemolytic anemia (AIHA) is a rare but potentially catastrophic hematological disorder characterized by the premature destruction of red blood cells mediated by autoantibodies targeting erythrocyte surface antigens.1 The condition is broadly classified into warm-type and cold-type AIHA based on the thermal reactivity of the autoantibodies, with warm-antibody AIHA (wAIHA) accounting for approximately 75% of cases.3 In the clinical setting of Indonesia, cases often present at advanced stages, requiring intensive transfusion support and nuanced immunosuppressive management.5 Case Report The analysis involves Ny. K, a 39-year-old female, who presented to the emergency department of a tertiary hospital in Bandar Lampung with a four-day history of profound weakness, dizziness, and gastrointestinal distress. Her clinical history revealed a two-year pattern of recurrent anemia and prior transfusions. Physical examination demonstrated a classic hemolytic triad: severe conjunctival pallor (anemia), scleral icterus (jaundice), and palpable splenomegaly. Laboratory investigations confirmed critical anemia with a hemoglobin level of 3 g/dl and a hematocrit of 11%. Evidence of hemolysis included significantly elevated lactate dehydrogenase (LDH) at 1344 IU/L and indirect hyperbilirubinemia at 3.3 mg/dl, while a reticulocyte count of 7.5% indicated a robust compensatory marrow response. The patient also reported a history of "susuk" (charm needle) implantation. Management strategies included high-volume packed red cell (PRC) transfusions (1200 cc), corticosteroid therapy with methylprednisolone, folic acid supplementation, and a specialized hepatobiliary nutritional protocol (Diet Hati III). Discussion The diagnostic workup for Ny. K is consistent with international protocols for identifying uncompensated hemolytic anemia, where peripheral destruction outpaces bone marrow production.8 The presence of splenomegaly and the biochemical markers suggest extravascular hemolysis, likely mediated by warm IgG autoantibodies.11 This report examines the challenges of blood transfusion in the presence of pan-agglutinins, the role of corticosteroids as first-line therapy, and the physiological significance of high LDH levels in predicting disease severity.1 Furthermore, the sociocultural aspect of "susuk" is explored, noting its biological inertness but radiological significance in diagnostic imaging.15 Conclusion Severe AIHA with anemia gravis represents a medical emergency requiring rapid stabilization through least-incompatible blood transfusions and high-dose immunosuppression. This case underscores the necessity of aggressive early intervention and the importance of excluding secondary causes, such as systemic lupus erythematosus or lymphoproliferative disorders, in the Indonesian clinical context. Continuous monitoring of reticulocyte response and hemolytic markers is vital to guide therapy and prevent relapses.